Chapter Dante nella Polonia del Quattro-Cinquecento. Dalla (s)fortuna di Dante ad alcune considerazioni sugli elementi costitutivi della letteratura polacca rinascimentale - Cabras, Francesco (Biblioteca di Studi di Filologia Moderna, 2022)
This article aims to show how Dante Alighieri was 'used' in Renaissance Polish literature. Dante was known by Polish intellectuals first of all as a political theorist. Only in the second half of the 14th century did Polish writers start to refer to him as a great poet (Długosz). However, Dante was rather known than read and 'used' as a topic character to demonstrate the excellence of vernacular poetry. Andrzej Trzecieski the Younger, in fact, wrote in a couple of epigrams to his friend Mikołaj Rej, that Rej is to Polish literature, what Dante (and Petrarch) was to Italian literature; in addition to this, Trzecieski underlines, through intertextual allusions, that Dante (and Rej) had the same dignity of ancient Greek and Latin poets. This attitude that vernacular literature is on par with Greek and ancient literature is found also in the elegy III 8 by Jan Kochanowski, where Ronsard is presented as a "classic" poet. The final part of this work compares the situation in 15th and 16th-century Italian and Polish literature in terms of the relationship between ancient and vernacular poetry.